The Effects of Dance Movement Therapy in the Treatment of Depression: A Multicenter, Randomized Controlled Trial in Finland - Hyvönen, Katriina; Pylvänäinen, Päivi; Muotka, Joona; Lappalainen, Raimo (Frontiers in Psychology, 2020)
This multicenter research investigates the effects of dance movement therapy (DMT) on participants diagnosed with depression. In total, 109 persons participated in the study in various locations in Finland. The participants were 39 years old, on average (range = 18–64 years), and most were female (96%). All participants received treatment as usual (TAU). They were randomized into DMT + TAU (n = 52) or TAU only (n = 57). The participants in the DMT + TAU group were offered 20 DMT sessions twice a week for 10 weeks in addition to standard care. The measurement points included pretreatment measurement at the baseline, posttreatment measurement at the end of the intervention, and a follow-up measurement 3 months afterward. The observed effects of the intervention among participants in the DMT+TAU group were a greater reduction in depression and in indicators of physical and psychological distress in comparison to the participants who received TAU-only. At the 3-month follow-up, the corrected between-group effect sizes (ESs) were medium and in favor of the DMT + TAU group (d = 0.60–0.72). These results are in line with the increasing number of research studies showing the benefits of DMT intervention among participants with depression, and these results indicate that DMT may improve the effectiveness of standard care. Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT04421651.